Pengaruh Media Online Google Classroom Terhadap Kepuasan Mahasiswa Keperawatan dalam Perkuliahan Bahasa Inggris - Fadhilah, Umu; Lizawati, Lizawati (UIR PRESS, 2023)
Online learning is a learning process that is carried out remotely without face to face but through internet media. Google Classroom is an Internet medium that can be used during courses, such as to send materials, discuss online, and to be able to create, deliver and edit assignments without using paper. Google Classroom facilities are implemented in the Nursing English course. The method used in this study is a quantitative descriptive method with percentage data analysis. The research tool used a questionnaire with research subjects namely nursing students who were taking basic English courses in Nursing. The results show that 50% of respondents are satisfied with the display available in the Google Classroom application. 70% of respondents are satisfied with the efficiency of using Google Classroom. Regarding ease of use, 56% of respondents were satisfied with the ease of use of this vehicle. The next factor that was also agreed upon was that 60% of respondents were satisfied with learning English using Google Classroom.